2006
DOI: 10.1124/mol.106.033282
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Evidence for a Protective Role of Heat Shock Factor 1 against Irritant-Induced Gastric Lesions

Abstract: Gastric lesions result from an imbalance between aggressive and defensive factors. Indirect lines of evidence suggest that heat shock proteins (HSPs) induced by various aggressive factors provide a major protective mechanism. In this study, we compared gastric ulcerogenic response in wild-type mice and in those lacking heat shock factor 1 (HSF1), a transcription factor for hsp genes. The severity of gastric lesions induced by ethanol or hydrochloric acid was worsened in HSF1-null mice. Immunoblotting, real-tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
30
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 47 publications
8
30
0
Order By: Relevance
“…A number of reports using HSF1-null mice and/or transgenic mice expressing HSP70 have shown that HSF1-dependent induction of HSP expression is protective against the development of various diseases, such as gastric ulcers, heart failure, pancreatitis, hypoxic/ischemic brain injury, and spinal and bulbar muscular atrophy (42)(43)(44)(45)(46). Because some HSPs have been reported to be overexpressed in the intestinal tissues of IBD patients (19,20,23) and in an animal model of IBD (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…A number of reports using HSF1-null mice and/or transgenic mice expressing HSP70 have shown that HSF1-dependent induction of HSP expression is protective against the development of various diseases, such as gastric ulcers, heart failure, pancreatitis, hypoxic/ischemic brain injury, and spinal and bulbar muscular atrophy (42)(43)(44)(45)(46). Because some HSPs have been reported to be overexpressed in the intestinal tissues of IBD patients (19,20,23) and in an animal model of IBD (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…Although we observed that the effects of GGA correlated with HSP72 induction, we could not completely prove that GGA improves glucose metabolism only through the HSP72-JNK pathway. It is necessary to assess the impact of the HSP72-JNK pathway using HSP72-knockout mice and/or HSF1-knockout mice (48) to determine whether the beneficial effects of GGA are exerted mainly through HSP72.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Hsf1 is required for normal development of the placenta, and female Hsf1 −/− mice are infertile (Xiao et al 1999;Christians et al 2000). Hsf1 −/− mice are more susceptible to lipopolysaccharide-induced mortality, cadmium-induced pulmonary damage, and hydrochloric acid-or ethanol-induced gastric lesions (Xiao et al 1999;Wirth et al 2004;Tanaka et al 2007). In the auditory system, Hsf1 −/− mice demonstrate increased susceptibility to noise trauma (Sugahara et al 2003;Fairfield et al 2005).…”
Section: Figmentioning
confidence: 99%